23⋅(6t+12)=28

Multiply both sides of the equation by 32.

32⋅23⋅(6t+12)=32⋅28

Simplify 32⋅23⋅(6t+12).

Cancel the common factor of 3.

Cancel the common factor.

32⋅23⋅(6t+12)=32⋅28

Rewrite the expression.

12⋅2⋅(6t+12)=32⋅28

12⋅2⋅(6t+12)=32⋅28

Cancel the common factor of 2.

Cancel the common factor.

12⋅2⋅(6t+12)=32⋅28

Rewrite the expression.

1⋅(6t+12)=32⋅28

1⋅(6t+12)=32⋅28

Multiply 6t+12 by 1.

6t+12=32⋅28

6t+12=32⋅28

Simplify 32⋅28.

Cancel the common factor of 2.

Factor 2 out of 28.

6t+12=32⋅(2(14))

Cancel the common factor.

6t+12=32⋅(2⋅14)

Rewrite the expression.

6t+12=3⋅14

6t+12=3⋅14

Multiply 3 by 14.

6t+12=42

6t+12=42

6t+12=42

Subtract 12 from both sides of the equation.

6t=42-12

Subtract 12 from 42.

6t=30

6t=30

Divide each term in 6t=30 by 6.

6t6=306

Cancel the common factor of 6.

Cancel the common factor.

6t6=306

Divide t by 1.

t=306

t=306

Divide 30 by 6.

t=5

t=5

Solve for t 2/3*(6t+12)=28